ACE Gene DD Genotype Association with Obesity in Pakistani Population - Amara Javaid (International Journal Bioautomation, 2011)
The renin-angiotensin system (RAS) has an established role in pathogenesis of metabolic etiologies. Angiotensin converting enzyme (ACE) is an important component of RAS that may influence metabolic outcomes in adipose tissue. The deletion “D allele”, of ACE gene I/D (insertion/deletion) polymorphism has been shown to be associated with rise in the serum level of ACE. This study is designed to correlate the association between ACE gene I/D polymorphism and obesity in adult population of Pakistan. Our study included 535 individuals; 147 normal with body mass index (BMI) 19-24.9, 183 overweight (BMI 26-29.9) and 205 obese (BMI > 30). The individuals were genotyped for ACE gene I/D polymorphism. The ratio of ACE gene II and ID genotypes were not significantly different among normal, overweight and obese individuals. However, the DD genotype in normal, overweight and obese individuals was 12.9%, 18.0% and 28.8% respectively. DD genotype is significantly high (P = 0.002) in obese than in overweight and normal individuals. Thus the results of this study may suggest a possible association of the D allele in adipogenesis and adipocyte metabolism by affecting the ACE plasma level.